Strategi Pemasaran Sayuran Hidroponik di Griya Hijau Hidroponik - Pinandhito, Aryo; Rochdiani, Dini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Griya Hijau Hidroponik, as one of the hydroponic vegetable suppliers in Bandung, faces challenges due to a decline in hydroponic vegetable sales caused by suboptimal marketing methods. This study aims to analyze the marketing strategy for hydroponic vegetables at Griya Hijau Hidroponik using the Business Model Canvas (BMC) approach and SWOT analysis. The main objective of this research is to understand the business performance of hydroponic vegetables and the marketing strategies implemented by Griya Hijau Hidroponik. The research method used includes SWOT analysis to identify internal and external factors affecting the business, as well as BMC to understand the business model applied. The results of the SWOT analysis indicate that Griya Hijau Hidroponik is positioned in Quadrant I, meaning the company is in a favorable condition with opportunities and strengths that can be maximized. Based on the findings, the recommended marketing strategies include utilizing certifications and expertise to produce high-quality products, expanding marketing to business consumer segments, and enhancing promotion and education through social media content. The implementation of these strategies is expected to improve the competitiveness and sustainability of Griya Hijau Hidroponik in the hydroponic agriculture industry.